(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
This article explores the importance, familiarity and applicability of Information and Communication Technologies (ICTs) for older people in the use of e-Gov services and in the quality of software development. A systematic literature review was used, with specific inclusion and exclusion criteria, analysing data from digital databases of articles collected between January and April 2024. The results indicate that, despite advances, older people still face significant barriers in accessing and using digital technologies. The importance of digital literacy is emphasised, as well as factors such as usability, security and portability, which are essential for the digital inclusion of this population.